Post-corona capitalism the alternatives ahead - Nölke, Andreas 1963- (Bristol University Press, 2022)
This book draws on comparative and international political economy to explore alternative options for future economic development in the wake of COVID-19. Covering all major infrastructures of contemporary capitalism affected by the pandemic, it analyses the impacts of the crisis on our global socio-economic-political systems